2016
DOI: 10.1016/j.invent.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, satisfaction and perceived efficacy of “ Space from Depression ” an internet-delivered treatment for depression

Abstract: BackgroundThere are clear advantages to internet-delivered interventions for depression. Users' perspectives on the acceptability, satisfaction, and efficacy of an internet-delivered treatment for depression can inform future developments in the area.MethodsRespondents (n = 281) were participants in an 8 week supported internet-delivered Cognitive Behaviour Therapy treatment for depressive symptoms. Self-report online questionnaires gathered quantitative and qualitative data on the user experience.Principle fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 24 publications
(32 reference statements)
10
51
0
1
Order By: Relevance
“…The positive alliance outcomes for completers showed that a strong therapeutic alliance can be established and maintained online (30,31). These results further align with client perceptions of the role of support in iCBT, where different studies have shown that clients found it helpful and motivating during the intervention period (71,72). The lack of change in perception of alliance for dropouts could be explained by the group receiving significantly less iCBT reviews and not getting enough contact to perceive an increase in alliance, which may take more time to develop in iCBT (73).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The positive alliance outcomes for completers showed that a strong therapeutic alliance can be established and maintained online (30,31). These results further align with client perceptions of the role of support in iCBT, where different studies have shown that clients found it helpful and motivating during the intervention period (71,72). The lack of change in perception of alliance for dropouts could be explained by the group receiving significantly less iCBT reviews and not getting enough contact to perceive an increase in alliance, which may take more time to develop in iCBT (73).…”
Section: Discussionsupporting
confidence: 69%
“…The current study sought to examine clinical outcomes and the alliance online in delivering the SilverCloud iCBT for depression and anxiety disorders as a prequel to face-to-face therapy for clients with severe symptoms of depression and anxiety. Based on previous research of the SilverCloud platform and programs (37)(38)(39), the following research questions were developed:…”
Section: Introductionmentioning
confidence: 99%
“…The current study was part of a larger randomised controlled trial of an Internet‐delivered intervention for the treatment of depression in a community sample, and for several reasons, the results are positive (Richards et al., , ). The use of the HAT measure allowed us to collect important data that gives us deeper insight and understanding of the important therapeutic processes that form the mechanics of an Internet‐delivered treatment such as the one examined.…”
Section: Resultsmentioning
confidence: 93%
“…Each program incorporated introductory quizzes, videos, informational content (including stories from other users), interactive activities, and a personal journal. More detailed information on the content of the platform can be found in the published protocol [15] and in previous research [17]. The standard recommendation was to complete one module per week over the 8-week period, with weekly reviews provided by the supporter.…”
Section: Interventionmentioning
confidence: 99%